Are there too many "times-to-pregnancy"? - Jørn Olsen (Nordic Association of Occupational Safety and Health (NOROSH), 2016)
The time between marriage and the birth of the first child has been used by demographers as a measure of fecundity, but such a measure only works if cohabitation and wanting to have a child are closely linked to marriage. In a world where pregnancies can be planned for those who have access to safe contraception methods, couples may know their "time-to-pregnancy" (TTP) as the waiting time from when they stopped using contraceptive methods until becoming pregnant or being classified as infertile (a period of ≥12 months). This TTP measure was first used in 1981 (1) as a measure of couple fecundity and it has been applied widely with success and failure in many areas of research including work-related fecundity problems (2, 3, 4). In this letter, some less well-known limitations of the TTP measure are discussed.